Quantification of the interactive motions of the atmospheric surface layer and a conifer canopy - Scannell , B (Cranfield University, 1983)
Consideration is given to the use of.vane (DVA) and propeller anemometers in the sensing of atmospheric turbulence. Careful experimental measurements of the DVA dynamic response contributes to this consideration. Quantification of the airflow within and above a Sitka spruce canopy then follows. Statistics indicate the non-Gaussianity of the air turbulence Such forms are interpreted through the intermittency of turbulence and investigated by a conditional sampling scheme. Nindspeed spectra have ragged forms, showing them to be vastly modified by the combined effects of the canopy-imposed scales, together with the canopy's elemental vortex shedding frequencies and resonances. Studies of tree motions show the possibility of_a simple connection between the resonances of the separate canopy elements, which could provide the tree with an atmospheric shock-absorbing structure, supportive of its observed response to turbulence The ensuing proposal of a hypothetical qualitative mechanical design principle based on aeroelastic similaritynay bebeneficial to the tree's survivability in conditions of strong atmospheric turbulence.